Kinetic ELISA in Microfluidic Channels - Yanagisawa, Naoki (Biosensors (Basel), 2011)
In this article, we describe the kinetic ELISA of Blue Tongue and Epizootic Hemorrhagic Disease viral antibodies in microfluidic channels by monitoring the rate of generation of the enzyme reaction product under static conditions. It has been shown that this format of the immunoassay allows very reliable quantitation of the target species using inexpensive glass microchips and a standard epifluorescence microscope system coupled to a CCD camera. For the viral antibodies assayed here, the limit of detection (LOD) for the analyte concentration in our microchips was established to be 3–5 times lower than that obtained on commercial microwell plates using a fiftieth of the sample volume and less than a third of the incubation time. Our analyses further show that when compared to the end-point ELISA format, the kinetic mode of this assay yields an improvement in the LOD by over an order of magnitude in microfluidic devices. This benefit is primarily realized as the observed variation in the background fluorescence (signal at the start of the enzyme reaction period) was significantly larger than that in the rate of signal generation upon repeating these assays in different microchannels/microchips. Because the kinetic ELISA results depend only on the latter quantity, the noise level in them was substantially lower compared to that in its end-point counterpart in which the absolute fluorescence measurements are of greater significance. While a similar benefit was also recorded through implementation of kinetic ELISAs on the microwell platform, the improvement in LOD registered in that system was not as significant as was observed in the case of microfluidic assays.